Melatonin and its therapeutic prospects in gastroenterology - A. A. Svistunov; Mikhail A. Osadchuk; A. M. Osadchuk (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To summarize modern scientific data on the role of melatonin in healthy people and in digestive diseases. To assess the role of melatonin drugs in gastroenterology and to outline its further application. Summary. Basic physiological functions of melatonin are discussed (biological rhythms, motor and evacuatory, cytoprotective, antioxidant, immunomodulating, anti-stress, antineoplastic etc.). The melatonin role in pathogenesis and prognosis of digestive diseases is covered. Results and perspectives melatonin containing drugs at functional and organic digestive diseases are discussed. Conclusion. The functional diseases and early manifestations of organic gastrointestinal diseases are usu-ally characterized by melatonin producing cell hyperpla-sia related to adaptive body response. At progression of organic disease, development of malignant neoplasms, hypoplasia of melatonin-producing cells was found, melatonin expression is decreased that indicates exhaustion of adaptive mechanisms. Adaptive properties of melatonin allow to recommend its therapeutic application at various disease groups as pathogenic treatment within basic modes of treatment.